Toward marker-assisted selection in breeding for fusarium wilt tropical race-4 type resistant bananas - Ferreira, C. F.; Chen, A.; Aitken, E. A. B.; Swennen, R.; Uwimana, B.; de Jesus Rocha, A.; da Silva Soares, J. M.; de Souza Ramos, A. P.; Amorim, E. P. (MDPI, 2024)
Fusarium wilt is a soil borne fungal disease that has devastated banana production in plantations around the world. Most Cavendish-type bananas are susceptible to strains of Fusarium oxysporum f. sp. cubense (Foc) belonging to the Subtropical Race 4 (STR4) and Tropical Race 4 (TR4). The wild banana diploid Musa acuminata ssp. malaccensis (AA, 2n = 22) carries resistance to Foc TR4. A previous study using segregating populations derived from M. acuminata ssp. malaccensis identified a quantitative trait locus (QTL) (12.9 cM) on the distal part of the long arm of chromosome 3, conferring resistance to both Foc TR4 and STR4. An SNP marker, based on the gene Macma4_03_g32560 of the reference genome ‘DH-Pahang’ v4, detected the segregation of resistance to Foc STR4 and TR4 at this locus. Using this marker, we assessed putative TR4 resistance sources in 123 accessions from the breeding program in Brazil, which houses one of the largest germplasm collections of Musa spp. in the world. The resistance marker allele was detected in a number of accessions, including improved diploids and commercial cultivars. Sequencing further confirmed the identity of the SNP at this locus. Results from the marker screening will assist in developing strategies for pre-breeding Foc TR4-resistant bananas. This study represents the first-ever report of marker-assisted screening in a comprehensive collection of banana accessions in South America. Accessions carrying the resistance marker allele will be validated in the field to confirm Foc TR4 resistance.